KAJIAN LITERATUR DAN SINTESIS ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) : SEBUAH STUDI REVIU SISTEMATIS - Ilmia Maulidah; Wahyu Agus Winarno (Akuntansi dan Teknologi Informasi, 2022)
This study aims to find out how the development of EMA research in 2000 - 2019. This research is a type of literature study research using secondary data sourced from the Publish Or Perish application and produces 5 publishers namely Elsevier, Emerald, Springer, Taylor & Francis, Wiley Online Library. Furthermore, the journals obtained from each publisher were analyzed to limit the quality of the journals by only using journals that were in the Q1 – Q3 range and indexed by Scopus. Article searches were carried out on each publisher's website page and 46 articles were found that matched the criteria. The data analysis technique used is a meta-analysis data analysis technique (forest plot). The results of the study stated that the Journal of Cleaner Production was the journal that carried out the highest publication for EMA research with a total of 15 articles published. The most productive researcher was obtained by Stefan Schaltegger with the number of EMA research publications as many as 6 articles. The keyword “Environmental Management Accounting” is the main word that often appears, followed by the keyword “Management Accounting”. Descriptive research methods are often used, followed by case and field study methods and trends in EMA research topics that can be used for future research including the implications of EMA on: manufacturing companies, universities, local governments.